Karakteristik, Metode Para Tokoh Wirausaha Sebagai Penunjang Dakwah Islam di Dunia Islam - Qanita Nailah Dzihni; Raesha Romesha; Salzabila Hadi; Adam Setiawan; Restu Ariq Nino Saputra; Muhammad Sirajuddin Akmal; Sugiarto (PT. Saha Kreasi Indonesia, 2025)
This study explains how the characteristics and work ethic of entrepreneurs can help spread the teachings of Islam, especially through business ethics and behavior that are in line with Islamic values. Since the early days of Islam, this has been done not only through verbal lectures, but also through economic activities that demonstrate good character, such as honesty, responsibility, discipline, and concern for the community. This study uses a literature review method by analyzing various written sources on entrepreneurship and da'wah. The results of the study show that building entrepreneurial traits can be done through education, motivation, direct experience, moral values, and examples from role models. Traits such as creativity, risk-taking, the ability to see opportunities, discipline, and good money management not only contribute to business success but also serve as a means of da'wah through exemplary behavior. Applying these traits in daily life can shape individuals who are productive, independent, and have good character, thereby contributing to community development and the wider dissemination of Islamic values. Thus, entrepreneurship plays an important role not only in the economic sphere but also in strengthening Islamic da'wah in a practical and sustainable manner.